If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + siny) * dx + (xcosy + siny) * dy = 0 Reorder the terms: (insy + x) * dx + (xcosy + siny) * dy = 0 Reorder the terms for easier multiplication: dx(insy + x) + (xcosy + siny) * dy = 0 (insy * dx + x * dx) + (xcosy + siny) * dy = 0 (dinsxy + dx2) + (xcosy + siny) * dy = 0 Reorder the terms for easier multiplication: dinsxy + dx2 + dy(cosxy + insy) = 0 dinsxy + dx2 + (cosxy * dy + insy * dy) = 0 dinsxy + dx2 + (cdosxy2 + dinsy2) = 0 Reorder the terms: cdosxy2 + dinsxy + dinsy2 + dx2 = 0 Solving cdosxy2 + dinsxy + dinsy2 + dx2 = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1dinsxy' to each side of the equation. cdosxy2 + dinsxy + dinsy2 + -1dinsxy + dx2 = 0 + -1dinsxy Reorder the terms: cdosxy2 + dinsxy + -1dinsxy + dinsy2 + dx2 = 0 + -1dinsxy Combine like terms: dinsxy + -1dinsxy = 0 cdosxy2 + 0 + dinsy2 + dx2 = 0 + -1dinsxy cdosxy2 + dinsy2 + dx2 = 0 + -1dinsxy Remove the zero: cdosxy2 + dinsy2 + dx2 = -1dinsxy Add '-1dinsy2' to each side of the equation. cdosxy2 + dinsy2 + -1dinsy2 + dx2 = -1dinsxy + -1dinsy2 Combine like terms: dinsy2 + -1dinsy2 = 0 cdosxy2 + 0 + dx2 = -1dinsxy + -1dinsy2 cdosxy2 + dx2 = -1dinsxy + -1dinsy2 Add '-1dx2' to each side of the equation. cdosxy2 + dx2 + -1dx2 = -1dinsxy + -1dinsy2 + -1dx2 Combine like terms: dx2 + -1dx2 = 0 cdosxy2 + 0 = -1dinsxy + -1dinsy2 + -1dx2 cdosxy2 = -1dinsxy + -1dinsy2 + -1dx2 Divide each side by 'dosxy2'. c = -1ino-1y-1 + -1ino-1x-1 + -1o-1s-1xy-2 Simplifying c = -1ino-1y-1 + -1ino-1x-1 + -1o-1s-1xy-2 Reorder the terms: c = -1ino-1x-1 + -1ino-1y-1 + -1o-1s-1xy-2
| Solve-3y-4=6y-19 | | s=-500+.10y | | 4x+3y=130 | | -26=-5x+3(x-8) | | 30.25=x^2-6x+39 | | -15/32/3/8 | | 4x-6+3x=6x-5+x | | x*1.25=y | | 5sin(x)+5=0 | | 2*sin(x)+5=-3*sin(x) | | 2sin(x)+5=-3sin(x) | | 2/3=-x/60 | | 3/4=-x/72 | | 3/10=-x/330 | | 1/5=-x/60 | | 28=8k-4 | | y=50+-.5x | | 3/4=-x/24 | | 20=7x+b | | 5b+8=38 | | 1/6=-x/24 | | f(x)=.2x^2-5 | | 9x+18=4x+23 | | 20t+19=93 | | -6x+3.9=8x+3.9 | | 8(x-1)-2x=(-x+50) | | 4[x+3]=-16 | | -8x-7x+9= | | x^4-x^2-25=0 | | 8[x+12]=96 | | 9x+22=4 | | 5p-6+2p+8=14+3p |